A Sociometric Analysis of Informal Communication among Indian Satellite Technologists - Sridhar, M. S. (Journal of Information and Knowledge, 1988)
By and large, librarianship seems to have ignored the informal communication flourishing among their clientele. Informal communication both within and with outside the organisation and various informal and interpersonal sources of information a found to play crucial role in the work of an engineer/technologist. Some of the reasons for such an importance of informal communication for an engineer are discussed. A study of interpersonal communication_looks at the 'transciever' role of an engineer and leads to inquire into his information potential and identification of communication networks, their characteristics like density, connectedness, centrality and cluster, communication stars, isolates and technological gatekeepers. The informal and interpersonal communication among a defined set of over 800 Indian satellite technologists is investigated by sciometric analysis of the number of persons they regularly contact for work related information and with the names of five most often contacted persons provided in response to a questionnaire. The intra and inter-organisation communication of respondents and their relation with Some characteristics of respondents are examined. A sociometric analysis of upto five most often contacted persons named by the respondents revealed that 391 respondents mentioned 515 individuals/organisations 1538 times. As much as 87% of contacts within the organisation and the rest represented inter-organisation communication. An average satellite technologist found to be simultaneously a source of information for about 3 others in the response population (connectedness of the network). The analysis helped identification of communication stars or high information potentials (HIPs), isolates and technological gatekeepers. An examination of dyadic reflexive communication revealed existance of a cluster and Some linking pins in the network. Further, similarities and dissimilarities of participants of dyadic communication are also analysed.